(untitled) (Avocetta, 2019)
Eleonora’s Falcon is well known for its delayed breeding season among European breeding raptors, however, its relatively prolonged pre-breeding period remains to date largely understudied. In this study, we compiled information on the species’ behaviour based on data from systematic field surveys to investigate activity patterns of Eleonora’s falcons during the pre-breeding period in an area that holds one of the largest colonies across its breeding range, namely the island of Antikythira in the southern edge of the Aegean Sea. According to our findings, large islands hosting Eleonora’s falcons breeding colonies may also constitute important foraging areas during the pre-breeding period as foraging was the main activity undertaken by the falcons. Foraging was mostly performed in areas where food availability, either staging birds or insects, is expected to be highest, namely in cultivated areas. Considering the habitat composition in the study area, previous findings on the spatiotemporal activity patterns of staging migrants and our opportunistic observations of foraging falcons, our findings suggest that birds could constitute an alternative food of source during this period of the year within our study area. Therefore, the revival of agricultural practices is expected to enhance local biodiversity and constitute a conservation priority for Eleonora’s falcons in the study area. Still, further studies are required to decipher the distribution pattern and habitat associations during the pre-breeding period of Eleonora’s falcons and ultimately guide conservation schemes at a larger spatial scale.